The Benefits, Challenges, and Future of Blockchain and The Internet of Things - Mufiidah, Andi Nabiilah; Destiani, Romanda Dwi (Blockchain Frontier Technology, 2023)
The Internet of Things (IoT) has expanded internet connectivity beyond computers andpeople to include most objects in our environment. The Internet of Things (IoT) can connectbillions of items at once, which has the effect of improving the need for information sharing andultimately enhancing our quality of life. Due to its centralized server/client approach, which limitsthe IoT's potential benefits, there are numerous obstacles to IoT adoption in the real world. Forinstance, the network's excessive number of IoT items can cause scalability and securityproblems. The server/client approach necessitates that all devices connect to and areauthenticated by the server, creating a single point of failure. As a result, shifting the IoT systemto a decentralized approach might be the best course of action. Blockchain is one of the mostwell-known decentralization technologies. The Blockchain is a potent technology thatdecentralizes administration and computation processes, which can address many IoTproblems, particularly security. The benefits and difficulties of the integration of the blockchainwith the IoT are highlighted in this paper's review. There is also a discussion of the potentialresearch avenues for blockchain and IoT. We conclude that combining blockchain technologywith IoT can result in a potent strategy that can significantly open the door for new businessmodels and distributed applications